Kreatif dengan Canva: Pelatihan Desain Grafis untuk Anak SDN 32 Kota Bengkulu - Muhammad Dwi Sandi; Hafriyuliani Hafriyuliani; Rekhoardriadi Rekhoardriadi (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2024)
Graphic design training with Canva for 5th grade students of SDN 32 Bengkulu City aims to imrove children’s understanding and basic graphic design skills. The interactive and fun training method introduces the use of Canva to create learning materilas such as posters and ifographics. The results showed a significant improvement in students techinacal abilities and creativity, with high enthusiasm and participation. Effective collaboration between teachers and the service team unsures smooth training. Positive feedvacl from participants and teachers confirmed the benefits of this training, equipping students with relevant digital skills the era of globalization.